Types I and II Keratin Intermediate Filaments - Jacob, Justin T. (Cold Spring Harb Perspect Biol, 2018)
Keratins—types I and II—are the intermediate-filament-forming proteins expressed in epithelial cells. They are encoded by 54 evolutionarily conserved genes (28 type I, 26 type II) and regulated in a pairwise and tissue type–, differentiation-, and context-dependent manner. Here, we review how keratins serve multiple homeostatic and stress-triggered mechanical and nonmechanical functions, including maintenance of cellular integrity, regulation of cell growth and migration, and protection from apoptosis. These functions are tightly regulated by posttranslational modifications and keratin-associated proteins. Genetically determined alterations in keratin-coding sequences underlie highly penetrant and rare disorders whose pathophysiology reflects cell fragility or altered tissue homeostasis. Furthermore, keratin mutation or misregulation represents risk factors or genetic modifiers for several additional acute and chronic diseases.